Variability, correlation, and path analysis in erect and prostrate cultivars of cowpea (Vigna unguiculata [L.] Walp.) - Araméndiz-Tatis, Hérmes; Espitia-Camacho, Miguel; Cardona-Ayala, Carlos (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The cowpea bean (Vigna unguiculata [L.] Walp.) is the most important legume in the Colombian Caribbean, and is cultivated with genotypes having prostrate growth habit, with yields that do not exceed 700 kg ha-1. Manual harvesting is very expensive for crop rotation in commercial agriculture, which is why cultivars with erect growth habit are required. The research was carried out in the first semester of 2022, in the experimental area of the Universidad de Córdoba (Monteria-Colombia). Sixteen erect genotypes and five prostrate genotypes, including the control, were evaluated under a randomized complete block design with five repetitions. Each experimental unit consisted of two rows of 5 m in length, with a distance between plants of 0.15 m and between rows of 0.40 m for a population density of 166.000 plants/ha. The results indicated genetic variability, which enables successful phenotypic selection, according to the estimated genetic parameters. Likewise, there was positive and significant correlations of performance components with yield. In addition, the unfolding of genotypic correlations by means of path analysis indicated that grain thickness is an important and easy to measure characteristic to increase yield.